EFFECT OF NITROGEN AND BIOFERTILIZER ON GROWTH OF CARNATION (DIANTHUS CARYOPHYLLUS L.) - Kumar, A.; RANA, G.S; DAHIYA, D.S. (Annals of Agricultural Research, 2014)
A pot experiment was conducted at the Department of Horticulture, CCS HaryanaAgricultural University, Hisar during 2004-05 to ascertain the effect of nitrogen andbiofertilizers on growth of carnation cv. Red Corso. Carnation cuttings were planted in pots lined with polythene sheet. Carnation cuttings were dipped in Azotobacter strains, suspension for half an hour before planting in pots in the monthof October. Five levels of nitrogen (0, 50, 100, 150 and 200 ppm) and five different strains of Azotobacter (0, HT-54, Mac-27, Mac-68 and MSX- 9) and their combinations were applied.The maximum number of branches were found where 150 ppm nitrogen was applied while it was minimum in control.The miximum number of branches per palnt were recorded in Mac-68 and minimum in control.Interaction between nitrogen and biofertilizer was non-significant for number of branches per plant.